SANGGAR SASTRA JAWA YOGYAKARTA DALAM PERSPEKTIF SOSIOLOGI TALCOTT PARSONS - Hayu Avang Darmawan (JENTERA: Jurnal Kajian Sastra, 2015)
Sanggar Sastra Jawa Yogyakarta is a literary group that focus on Javanese literature in D.I.Yogyakarta. The purpose of this research is to discover and explain the establishment and Sanggar Sastra Jawa Yogyakarta system that is able to survive for a long time. It was given a lot of group Javanese literature in East Java, Central Java, and Yogyakarta that appear but can not last long. The analysis used is the social system theory developed by Talcott Parsons. The theory explains the four functional requirements, that is latent pattern-maintenance, integration, goal attainment, adaptation as a requirement for the system to survive in a long time. Further descriptive method is used, with data collection through participant observation and in-depth interviews, and the data is written. Informants consisted of administrators and members of the group. The results of the study found that the Operasi Tertib Remaja in 1966 and the elimination of regional language lessons by the education minister of the 1970s was able to immobilize the joints of Javanese literature. Furthermore, emerging awareness group of people to maintain their identity by setting up Sanggar Sastra Jawa Yogyakarta. The group was able to survive by maintaining system adaptation by uniting themselves with government agencies, have short and long term goals, integrity harmonization that is able to be maintained, and renegeration pattern with internalization value and norm. AbstrakSanggar Sastra Jawa Yogyakarta merupakan sanggar sastra yang fokus pada sastra Jawa di D.I.Yogyakarta. Tujuan penelitian ini adalah menemukan dan menjelaskan pendirian dan sistem Sanggar Sastra Jawa Yogyakarta yang mampu bertahan dalam kurun waktu lama. Hal itu mengingat banyak sanggar sastra Jawa di Jawa Timur, Jawa Tengah, dan Yogyakarta yang muncul namun tidak dapat bertahan lama. Analisis yang digunakan adalah teori sistem sosial yang dikembangkan Talcott Parsons. Teori tersebut menjelaskan empat kebutuhan fungsional, yaitu latent pattern-maintenance, integration, goal attainment, adaptation sebagai syarat sebuah sistem untuk mampu bertahan hidup dalam kurun waktu yang lama. Selanjutnya digunakan metode deskriptif, dengan pengambilan data melalui observasi terlibat dan wawancara mendalam, serta data-data tertulis. Informan terdiri atas pengurus dan anggota sanggar. Hasil dari penelitian diketahui bahwa Operasi Tertib Remaja tahun 1966 dan penghapusan pelajaran bahasa daerah oleh menteri pendidikan era 1970an mampu melumpuhkan sendi-sendi sastra Jawa. Selanjutnya, timbul kesadaran sekelompok orang untuk mempertahankan identitasnya dengan mendirikan Sanggar Sastra Jawa Yogyakarta. Sanggar tersebut mampu bertahan dengan memelihara sistem adaptasi dengan menyatukan diri dengan lembaga pemerintahan, memiliki tujuan jangka pendek dan panjang, harmonisasi integritas yang mampu dijaga, serta pola renegerasi dengan internalisasi nilai dan norma.